Effects of some selected stabilizer additives on the stability of pasteurized carabao's milk during refrigerated storage - Laurio, Mary Grace P.; Acevedo, Teresita P. (2005., 2005)
ABSTRACT Four (4) stabilizers in varying concentrations and combination (xanthan gum, CMC, guar gum and carrageenan) were evaluated for their effects on the stability of pasteurized carabao's milk (PCM) to determine which is the best stabilizer. The results showed that the combination of guar gum and carrageenan at 1.6ppt and CMC at 1ppt are effective in maintaining the stability of PCM monitored in terms of its cream separation flocculation, annd sedimentation. Using the two most effective stabilizers, guar gum and carrageenan combination and CMC, PCM was further evaluated for adequacy of the pasteurization process by determining its microbiological quality as well as its changes in pH. The pasteurization process was evaluated to be adequate rendering the PCM safe for consumption upto five (5) days at refrigerated storage. A duo-trio test was further conducted to evaluate which of the two PCM with added stabilizer closely approximate the PCM without any stabilizer additive. General acceptability test showed that the PCM with CMC at 1ppt is acceptable in all its sensory attributes.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Food additives; Milk